Lexical Cohesion in Zootopia - Setiawan, Harry; Simatupang, Ervina C.M. (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research delves into the intricate examination of lexical cohesion within the dialogues of the main characters, Hoops and Nick, in the animated movies Zootopia (2016) by Byron Howard and Rich Moore. Grounded in the qualitative research methodology, the study aims to determine the various types of lexical cohesion present and to analyze the functions of each cohesion device employed, drawing upon Halliday and Hasan's theory (1976, p. 282). Through meticulous analysis, the research identifies 168 instances of lexical cohesion, including 76 repetitions (45.8%), 2 synonyms (1.2%), 1 antonym (0.6%), 2 hyponyms (1.2%), 1 meronym (0.6%), and 86 collocations (51.8%). The prevalence of collocations underscores their significant role in reinforcing themes, character dynamics, and plot advancement within the narrative framework. By shedding light on these linguistic mechanisms, the study contributes to a deeper understanding of storytelling and character development in animated movies, advancing the current state of knowledge in the field of linguistics studies. . Keyword: Discourse analysis; cohesion; lexical cohesion; animation movies.